2022
DOI: 10.1155/2022/3982335
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants Associated with Chronic Obstructive Pulmonary Disease Risk: Cumulative Epidemiological Evidence from Meta-Analyses and Genome-Wide Association Studies

Abstract: Background. Last two decades, many association studies on genetic variants and chronic obstructive pulmonary disease (COPD) risk have been published. But results from different studies are inconsistent. Therefore, we performed this article to systematically evaluate results from previous meta-analyses and genome-wide association studies (GWASs). Material and Methods. Firstly, we retrieved meta-analyses in PubMed, Embase, and China National Knowledge Infrastructure and GWASs in PubMed and GWAS catalog on or bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…The present study identifies the potential genetic variants of the following genes: FAM13A, CHRNA, ADAM33, GSTM1, TNF-α, VDBP, HHIP, and HMOX1 [12]. These genes are involved in lung development, repair, and function, but their exact role in COPD is not yet fully understood.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The present study identifies the potential genetic variants of the following genes: FAM13A, CHRNA, ADAM33, GSTM1, TNF-α, VDBP, HHIP, and HMOX1 [12]. These genes are involved in lung development, repair, and function, but their exact role in COPD is not yet fully understood.…”
Section: Discussionmentioning
confidence: 97%
“…Covariates: age, residence area, gender, BMI, job history in chemical and dust-related companies, smoking status, drinking status, total physical activity, and energy intake. The cutoff of each parameter: 1 100% of estimated energy requirement (EER), 2 70 energy percent (En%) of carbohydrates, 3 15 En% of protein, 4 15 En% of fat, 5 0.7 En% of w-3 fatty acid, 6 4.5 En% of w-3 fatty acid, 7 20 g/day of fiber, 8 75th percentile of each intake, 9 DRI of each nutrient (100 mg for V-C, 10 mg for V-E, 10 ug for V-D, and 50 ug for Se), 10 500 mg/day of Ca, 11 20 g/day of alcohol, 12 150 min/week of moderate exercise. *** Significantly different from the Health group.…”
Section: Nutrient Intake and Lifestyle Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rs2071288 and rs2070600 have been previously associated with sRAGE levels [ 14 ], COPD risk [ 40 ], pulmonary function parameters [ 20 ], emphysema, and pulmonary fibrosis [ 41 ]. We did not observe any association for the rs2071288; however, the CT genotype of the rs2070600 was found to have a low COPD risk strongly influenced by age as a covariate.…”
Section: Discussionmentioning
confidence: 99%
“…Two meta-analyses were previously conducted to investigate the association between the TNF-α -308 G/A (rs1800629) variant and COPD risk. One study revealed that this variant was significantly associated with COPD risk in the Asian population, but this association was no longer significant after adjusting for smoking (26). Another study showed that individuals with the G/G and G/A genotypes have a lower risk of developing COPD compared with A/A genotype carriers (27).…”
Section: Discussionmentioning
confidence: 99%